2016
DOI: 10.1002/mar.20954
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Taxonomy of Virtual Communities from a Value Cocreation Perspective

Abstract: The enormous growth that social networks have experienced in recent years has caused firms to begin to view social networks as enabling environments for supplier-customer interactions. It has been argued that company behavior influences customer participation; however, this notion has rarely been investigated. Therefore, the purpose of this research is twofold as follows: to determine if there are differences among virtual communities regarding customer participation and define the main factors that can cause … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Research inspired by the original concept showed the practical value of customer participation, consumers' emotional and quasireligious investment in brands, and the practices of value creation that take place in communal settings such as brand fests (McAlexander, Schouten, & Koenig, 2002;Schau et al 2009). Since then, the brand-oriented behaviour of consumers (as well as brand managers) has received an increasing level of attention and analysis from marketing and consumer researchers across the globe (for recent work see Mousavi, Roper, & Keeling, 2017;Rodríguez-López & Diz-Comesaña, 2016;Scarpi, 2010;Schrembri & Latimer, 2016;Skalen, Pace, & Cova, 2015;Steinmann, Mau, & Schramm-Klein, 2015;Teichmann, Stokburger-Sauer, Plank, & Strobl, 2015). Research has examined the lifecycles of brand communities (Muniz and Schau 2005;Wang & Ding, 2017), when communities fail because value is not created (Gambetti & Graffigna, 2015), and when communities actively go out to damage or reject a brand (Parmentier & Fischer, 2015).…”
Section: Brand Communitymentioning
confidence: 99%
“…Research inspired by the original concept showed the practical value of customer participation, consumers' emotional and quasireligious investment in brands, and the practices of value creation that take place in communal settings such as brand fests (McAlexander, Schouten, & Koenig, 2002;Schau et al 2009). Since then, the brand-oriented behaviour of consumers (as well as brand managers) has received an increasing level of attention and analysis from marketing and consumer researchers across the globe (for recent work see Mousavi, Roper, & Keeling, 2017;Rodríguez-López & Diz-Comesaña, 2016;Scarpi, 2010;Schrembri & Latimer, 2016;Skalen, Pace, & Cova, 2015;Steinmann, Mau, & Schramm-Klein, 2015;Teichmann, Stokburger-Sauer, Plank, & Strobl, 2015). Research has examined the lifecycles of brand communities (Muniz and Schau 2005;Wang & Ding, 2017), when communities fail because value is not created (Gambetti & Graffigna, 2015), and when communities actively go out to damage or reject a brand (Parmentier & Fischer, 2015).…”
Section: Brand Communitymentioning
confidence: 99%